دور العلامة التجارية في تحقيق التنمية الاقتصادية (مجلة الواحات للبحوث والدراسات, 2021)
The Brand Is Known Since Antiquity, The Traders Exploited It In The Commercial Business, And They Knew Their Development Well, They Have Designed Various Symbols And Labels. A Variety Consists Of The Mark And Placed On The Goods And Goods, And Services It Is Distinguished For Easy Identification During Commercial Transactions In Order To Avoid Mixing And Ensuring Their Protection In The Market.With The Expansion Of Trade And The Increase Of Trades And Professions, Especially After The Progress Of The Industrial Revolution In Europe States Have Initiated An International Convention Relating To The Protection Of Industrial And Commercial Property Rights In Addition To Calling For The Enactment Of National Laws Ensuring Protection For Its Role And Profound Impact On Various Aspects Of Economic And Social Life, What He Sometimes Promoted To The Political Dimensions, When It Comes To Big Companies, Who Have Distinctive Marks Their Economic Interests Overlap With Political Power In The Country To Which They Belong, Or Can Become A Means Of Economic And Political Pressure In Other Countries. That's Why The Brand Has Assumed A Prestigious Position In The Areas Of Economic Development ,Ensuring The Effective Protection And Control Of The Products Of Natural Or Legal Persons.In This Context Algerian Law Was Concerned With Brands And Regulated Them, In Order To Keep Pace With The Current Economic Transformations. Algerian Law Was Concerned With Trademarks, And Regulate It And Modified Depending On The Case, To Keep Pace With Current Economic Transformations; And Keep Up The Pace Of International Trade Liberalization Agreements, And Their Effects On Economic Aspects. Keywords -Brand - Industrial Property - The Product - Economic Development - Trademark Registration